Reporting a Case of Bone Tuberculosis on Child - Santos, Fabiana Cristina Fulco; Nascimento, André Luiz Alves do; Lira, Laís Ariane de Siqueira; Lima, Juliana Figueirêdo da Costa; Montenegro, Rosana de Albuquerque; Montenegro, Lilian Maria Lapa; Schindler, Haiana Charifker (Challenges in Disease and Health Research Vol. 5, 2021)
Bone tuberculosis (TB) is one of the forms of extrapulmonary tuberculosis that affects, above all, the spine, long bones and joints. The authors report a case of a 12-year-old child with a complaint of pain and deformity in the lower thoracic region that had lasted for two years. Clinical, epidemiological and laboratory characteristics associated with images of apparent damage in the T9-T10 and T11-T12 vertebrae taken by radiography of the thoracic spine and nuclear magnetic resonance in addition to the positivity of the molecular test based on the polymerase chain reaction, led to tuberculous spondylitis being diagnosed and specific therapy was started. Culture of vertebral biopsy was positive for Mycobacterium tuberculosis after thirty days. The early detection of disease and referral to a specialist service for rapid diagnostic’s investigation are measures that helps on patient prognosis. It should be a concern of pediatricians when they come across chronic cases of back pain and arthralgia in endemic areas.